2008
DOI: 10.1111/j.1365-2222.2008.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 2 agonist Pam3CSK4 enhances the induction of antigen‐specific tolerance via the sublingual route

Abstract: Pam3CSK4 induces Th1/regulatory T cell responses, and as such, is a valid candidate adjuvant for sublingual allergy vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…Pam3CSK4 reverses established OVA-induced airway inflammation by a mechanism that is critically dependent on IL-12 but not IL-10 or TGF-b (5,6). In a murine model of asthma, Pam3CSK4 was shown to be a valid candidate adjuvant for sublingual allergy vaccines that mediated Th1/Treg cell responses (30). In the present study, we first demonstrated in humans that Pam3CSK4 activates CD8 +…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Pam3CSK4 reverses established OVA-induced airway inflammation by a mechanism that is critically dependent on IL-12 but not IL-10 or TGF-b (5,6). In a murine model of asthma, Pam3CSK4 was shown to be a valid candidate adjuvant for sublingual allergy vaccines that mediated Th1/Treg cell responses (30). In the present study, we first demonstrated in humans that Pam3CSK4 activates CD8 +…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies suggested that the induction of CD4 + Treg cells might be associated with suppression of allergic responses in patients after successful IT (25). It was demonstrated that the TLR2 synthetic agonist Pam3CSK4 has therapeutic potential to decrease the mite allergen-induced Th2 immune response (28,29); thus, it may be useful as an adjuvant in immunotherapy for allergic disease (30). Our study investigated whether Dermatophagoides pteronyssinusspecific IT can enhance CD8 + Treg populations, as well as whether Pam3CSK4 increases CD8 +…”
Section: Cd25mentioning
confidence: 99%
“…By exploiting a human in vitro allergy model, we tried to predict the potential of BPPcysMPEG to modulate antigen presenting cells and a subsequent allergen-specific immune response. Antigen presenting cells play a decisive role in the induction of immune responses and modulation of this cell population might influence T cell polarization (Lombardi et al, 2008). The stimulation of iDC with BPPcysMPEG with or without the presence of the allergen caused maturation of these cells, as indicated by the upregulation of co-stimulatory molecules and the secretion of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of allergic asthma by immunomodulation or regulation of the adaptive immune system via manipulation of innate immune processes is an attractive therapeutic strategy. Ligands of the TLR family, such as the synthetic lipoprotein PAM3CSK4 (2,3), LPS (4-6), resiquimod (7,8), and CpG oligodeoxynucleotides (9,10), which activate TLR2, TLR4, TLR7/8, and TLR9, respectively, are capable of inhibiting experimental allergic asthma in animal models. In this context, we examined the immunomodulatory potential of Protollin, a mucosal vaccine adjuvant composed of TLR2 and TLR4 ligands, in a murine model of experimental allergic asthma (11).…”
mentioning
confidence: 99%